PHYTOCHEMICAL REMEDIAL REACTION OF BLACK PEPPER (Piper nigrum) EXTRACT AGAINST FUNGAL TUBER ROT PATHOGEN OF SWEET POTATO (Ipomoea batata) - Iwuagwu, Christian Chukwunenye; Ozonebechi, MargretMary C.; Nwolisah, Sylvia O. (FUDMA JOURNAL OF SCIENCES, 2025)
Tubers of sweet potato serve as a staple food in Nigeria and also used for industrial production of starch, sugar and alcohol. However, production of this valuable tuber crop suffers from several constraints especially poor tropical storage conditions and postharvest microbial deterioration. An experiment was carried out at the research Laboratory of Plant Pathology of Crop Science and Horticulture, Nnamdi Azikiwe University, Awka to investigate the phytochemical effect of black pepper (Piper nigrum) extract on fungal tuber rot pathogen of sweet potato (Ipomoea batata). The experiment was a 2 x 4 factorial laid out in a Completely Randomized Design (CRD) and replicated three times. The factors were 2 extracting solvents: ethanol and N-hexane, while the other factors were four concentration levels of the two plant extracts (0%, 50%,75% and 100%). A poison method was applied where a 5cm discs of mycelia of the test fungus collected from the interface of the point of active growth of the fungus of a 7-day pure culture and placed in the center of petri dishes containing 5mls of the Piper nigurum extracts of various concentrations fortified with few drops of lactic acid. Plates were incubated at room temperature (28ºC ± 2) on laboratory benches and observed for eight days during which radial inhibition was measured and recorded. Results showed that fungal organism such as Fusarium solani, Fusarium oxysporum and Mucor circinelloides were implicated as the causal agents of sweet potato tuber rot.  The phytochemical used was found to be very effective in controlling...
Keywords: Reaction; Phytochemical; Concentration; Black Pepper; Organisms